The Rupa Book Of Scary Stories - Ruskin Bond (Rupa Publication, 2013)
Thirteen hair-raising stories to make your flesh creep. Here are literary masterpieces by Kipling, Saki, Algernon Blackwood and others with tales filled with chilling terror and unfathomable horror.
Keywords: Mystery -- Mystery